URGENSI GURU SEJATI DI SEKOLAH DASAR - Samino, Samino (Universitas Muhammadiyah Surakarta, 2014)
True teacher, the substance is a true example of a teacher, tireless , hard work, struggleand sacrifice for the success of his students. Teachers have a minimum three main tasks,namely: (1) professional duties, (2) human duty, and (3) civic duties. Furthermore, withregard to who the true teacher? There are five important things attached as a trueteacher, namely: (1) the teachers are second parents, (2) the teacher is a motivator, (3)the teacher is the adventurous, (4) teacher, liberator and fighters, and (5) teacher, personalprophetic spirit. To be able to be a true teacher, five elements must be attached,namely: (1) responsibility , not a privilege, (2) the sacrifice, not the facility, (3) Workhard , not relaxed; (4) Authority, not authoritarian, and (5) Modeling. True teacher isfully teachers in goodness, not tempted by the glitter of the world. If teachers are temptedby the glitter of the world, they will ruin their students and even society. Hope all thechildren of this nation remains a good teacher or professional teachers who meet thecompetency of personality, pedagogic, social, and professional as well as the Holy Prophet(Siddeeq, trustworthy, sermons, and fathonah). They Eventually bring success for theglory of Indonesian education.